2015
DOI: 10.3233/jad-142874
|View full text |Cite
|
Sign up to set email alerts
|

Tau Aggregation Inhibitor Therapy: An Exploratory Phase 2 Study in Mild or Moderate Alzheimer's Disease

Abstract: Abstract.Background: As tau aggregation pathology correlates with clinical dementia in Alzheimer's disease (AD), a tau aggregation inhibitor (TAI) could have therapeutic utility. Methylthioninium (MT) acts as a selective TAI in vitro and reduces tau pathology in transgenic mouse models. Objective: To determine the minimum safe and effective dose of MT required to prevent disease progression on clinical and functional molecular imaging outcomes. Methods: An exploratory double-blind, randomized, placebo-controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
164
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(173 citation statements)
references
References 36 publications
4
164
0
5
Order By: Relevance
“…The majority of trials (n = 94) used at least one cognitive outcome, 25,27-29, 51,52,55,57,64,66,68,75,78,[86][87][88][89][90][91][92][93]97,104,106,107,110,112,115,118,119,121,123,125,126,130,131,133,134,[137][138][139][140]143,145,146 with a variety of 16 measures used. ADLs were measured in 55 trials, using 12 measures.…”
Section: Published Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of trials (n = 94) used at least one cognitive outcome, 25,27-29, 51,52,55,57,64,66,68,75,78,[86][87][88][89][90][91][92][93]97,104,106,107,110,112,115,118,119,121,123,125,126,130,131,133,134,[137][138][139][140]143,145,146 with a variety of 16 measures used. ADLs were measured in 55 trials, using 12 measures.…”
Section: Published Trialsmentioning
confidence: 99%
“…ADLs were measured in 55 trials, using 12 measures. 27,28,33,37,41,45,46,49,51,52,54,55,57,59,61,63,64,66,68,77,78,81,[85][86][87][88][89][90]92,97,104,[106][107][108][110][111][112]114,115,118,119,[121][122][123][124][125]128,134,135,137,138,[142][143][144][145] Biological markers were measured in 51 trials using a variety of nine biological t...…”
Section: Published Trialsmentioning
confidence: 99%
“…Modulation of autophagy has entered to the main stage of AD drug development. Recently, the promising findings of the old compound, methylthioninium chloride (methylene blue) inhibits Tau aggregation through inducing autophagy [54,55]. At nanomolar concentrations, MB can reduce Tau levels in both organotype brain slices from the mouse model of frontal-temporal dementia (FTD).…”
Section: Discussionmentioning
confidence: 99%
“…The purported action of both of these compounds is to act as tau aggregation inhibitors by not only inhibiting the formation of new oligomers, but more importantly to release soluble tau from oligomers and paired helical filaments in a monomeric form which is susceptible to proteases (97). In a large 12-month phase II study in 321 subjects, MTC was found to stabilize the progression of AD over 50 weeks in both mild and moderate AD (98). The more stable, reduced version of methylthioninium, LMTX, was tested in two parallel phase III studies in AD in 250 centers in 22 countries world-wide enrolling 891 patients with mild-to-moderate AD (NCT01689246) completed at the end of 2015 and in 800 patients with mild AD (NCT01689233) completed in June 2016.…”
Section: Chf-5074mentioning
confidence: 99%